Isolasi dan identifikasi bakteri asam laktat dari pangan fermentasi berbasis ikan (Inasua) yang diperjualbelikan di Maluku-Indonesia - Adde Lolita Putri; Endang Kusdiyantini (Jurnal Biologi Tropika, 2018)
Lactic acid bacteria are beneficial bacteria for the health of the body by improving the balance of the intestinal microflora. Lactic acid bacteria can generally be isolated from fermented foods, fruits, vegetables and meat. Inasua is a traditional fermented fish product originating from Central Maluku (Teon, Nila and Serua islands) wherein the fermentation process is carried out at room temperature for a certain time. The purpose of this study was isolation and identification based on the morphological characteristics of lactic acid bacteria in inasua. Isolation of Lactic Acid Bacteria was carried out using the pour plate method and the streak method on the media de Man, Rogosa and Sharpe Agar (MRSA) and Nutrient Agar media. The culture was incubated at 370C for 48 hours. The growing colonies were observed for morphological characteristics and GRAM staining of bacteria was carried out. The results of isolation of BAL from inasua in the media de Man, Ragosa and Sharpe Agar (MRSA) + CaCO3 obtained 4 bacterial isolates, namely INS-A1, INS-A2, INS-A3 and INS-A4 and only 2 isolates that have the characteristics of positive GRAM with Bacillus forms, namely INS-A2 and INS-A4. It is suspected that the 2 isolates were isolates of Lactic Acid Bacteria. The results of isolation on Nutrient Agar (NA) media contained 5 isolates namely INS-B1, INS-B2, INS B3, INS-B4, INS-B5 which have characteristics as negative GRAM shaped Bacillus